Identification and Characterization of Base-Substitution Mutations in the Macronuclear Genome of the Ciliate Tetrahymena thermophila. (4th November 2020) - Wang, Guangying; Fu, Lu; Xiong, Jie; Mochizuki, Kazufumi; Fu, Yunxin; Miao, Wei
Abstract: Polyploidy can provide adaptive advantages and drive evolution. Amitotic division of the polyploid macronucleus (MAC) in ciliates acts as a nonsexual genetic mechanism to enhance adaptation to stress conditions and thus provides a unique model to investigate the evolutionary role of polyploidy. Mutation is the primary source of the variation responsible for evolution and adaptation; however, to date, de novo mutations that occur in ciliate MAC genomes during these processes have not been characterized and their biological impacts are undefined. Here, we carried out long-term evolution experiments to directly explore de novo MAC mutations and their molecular features in the model ciliate, Tetrahymena thermophila . A simple but effective method was established to detect base-substitution mutations in evolving populations whereas filtering out most of the false positive base-substitutions caused by repetitive sequences and the programmed genome rearrangements. The detected mutations were rigorously validated using the MassARRAY system. Validated mutations showed a strong G/C→A/T bias, consistent with observations in other species. Moreover, a progressive increase in growth rate of the evolving populations suggested that some of these mutations might be responsible for cell fitness. The established mutation identification and validation methods will be an invaluable resource to make ciliates an important model system to study the role of polyploidy in evolution.